Spatial Mobility as a Value. Polish Migrations in the Second Decade of the 21st Century before the COVID-19 Pandemic - Bączyńska, Ewa Maria (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
Mobility is an appreciated feature of specific objects, devices, financial resources, services and so on. However, as this study is of a sociological nature, I omitted discussing the mobility of entities other than human beings. Therefore, this article is based on an example of Polish foreign migrations in the second decade of the 21st century before the COVID-19 pandemic. Mobility is being perceived here as a valuable measure to achieve selected goals. The main part of this study is a comparative analysis of a selection of reports from quantitative research performed by the Public Opinion Research Centre (CBOS). This study provides answers, amongst others, to the following questions: How did the level of participation of Poles in foreign migrations and their destinations change in years 2010–2019? What are the differences between participation in the spatial mobility of Poles from various socio-demographic backgrounds? And most importantly what motives contribute to their decisions?